Teacher Training in Inquiry-Based Learning in Social Studies in Cambodia - Bun Pichchenda (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2024)
This case study aimed to explore the characteristics, level of implementation, and challenges of training Inquiry-Based Learning (IBL) in Cambodia, specifically focusing on the social studies subject used in Provincial Teacher Training Centers (PTTCs) and Primary Schools. This study, researcher focuses on mix group are teacher trainers and initial primary school teachers. Researcher have put forward a hypothesis stating that an inquiry-based learning model addresses the limitations found in traditional learning methods. This study, researcher found that both teacher trainers and initial primary school teachers held a positive perception of the IBL approach due to its ability to promote critical thinking and students' engagement. In teacher training centers, the level of IBL implementation in social studies was primarily at level 2, known as "guided inquiry." In primary schools, the level of IBL implementation in social studies was mostly at level 1, referred to as "structured inquiry." In conclusion, social studies, as a subject area, deals with complex and real-world issues, making it an excellent domain for implementing IBL. Through inquiry-based learning, students can explore historical events, analyze societal structures, and understand global challenges in a more engaging and interactive manner.